2023
DOI: 10.3389/fonc.2023.1097956
|View full text |Cite
|
Sign up to set email alerts
|

Emerging landscape of circFNDC3B and its role in human malignancies

Abstract: In recent years, more attention has been paid to expanding the abundance of Circular RNAs (circRNAs), while the circRNAs that have been found to have significant functions have not been studied in different diseases. CircFNDC3B is one of the most researched circRNAs generated from fibronectin type III domain-containing protein 3B (FNDC3B) gene. Accumulating researches have reported the multiple functions of circFNDC3B in different cancer types and other non-neoplastic diseases, and predicted that circFNDC3B mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 131 publications
0
5
0
Order By: Relevance
“…We ultimately identified 11 circFNDC3B candidates that capable of translating proteins among 65 circFNDC3Bs via circRNADb and TransCirc database. Among the top five candidates, hsa_circ_0001361 and hsa_circ_0006156 have been reported in oral cancer and colon cancer [ 12 ], and the primers for hsa_circ_0006948 and hsa_circ_0005700 were not successfully designed. Therefore, we selected circ0003692 for intensive study (Additional file 1: Table S7 , Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We ultimately identified 11 circFNDC3B candidates that capable of translating proteins among 65 circFNDC3Bs via circRNADb and TransCirc database. Among the top five candidates, hsa_circ_0001361 and hsa_circ_0006156 have been reported in oral cancer and colon cancer [ 12 ], and the primers for hsa_circ_0006948 and hsa_circ_0005700 were not successfully designed. Therefore, we selected circ0003692 for intensive study (Additional file 1: Table S7 , Fig.…”
Section: Resultsmentioning
confidence: 99%
“…CircFNDC3B, derived from the gene FNDC3B, stands as one of the extensively studied circRNAs. Fourteen studies have investigated the diverse functions of circFNDC3B in various diseases [ 12 ]. For example, Hong et al demonstrated that circFNDC3B promoted the migration and invasion of GC cells by regulating the expression of E-cadherin and CD44 [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…further revealed that the high expression of circFNDC3B in serum exosomes is directly associated with the occurrence and development of esophageal squamous cell carcinoma, possibly serving as an independent risk predictor for aiding in early diagnosis ( 29 ). CircfNDC3B not only affects tumor cells through exosomal transfer but also functions through the miR-490–5p/TXNRD1 axis, further driving the progression of esophageal squamous cell carcinoma ( 30 ). Transfection of exosomal circ-CYP24A1 can inhibit the malignant behavior of cutaneous squamous cell carcinoma, offering new possibilities for noninvasive therapeutic strategies and potentially serving as a diagnostic marker ( 31 ).…”
Section: The Role Of Exosomal Circrnas In the Diagnosis And Progressi...mentioning
confidence: 99%
“…Unlike linear RNAs, circRNAs have a steady, conserved, covalent loop structure and are resistant to degradation by exonuclease in the cytoplasm due to having a unique continuous loop structure and not having 3′ and 5’ ends [ 85 ]. Because of their high stability, circRNAs are known as biomarkers for diagnosis, prognosis, and prediction of response to treatment in body fluids (urine, plasma, exosomes, etc.)…”
Section: Introductionmentioning
confidence: 99%